EVALUATING THE SCHOOL TEXTBOOKS FROM THE PERSPECTIVE OF STUDENTS - Rahmayani; Sani, Anwar; Selle, Amzah (Prodi Tadris Bahasa Inggris STAIN Parepare (IAIN Parepare), 2018)
This research examined about the students? need on the textbook and whether it is fulfilled their needs. The purpose was to find out the textbook acceptablity by analyzing the students? needs on their textbook according to the students opinion on it. This research used triangulation method such as interview, questionnaire, and observation. The primary data was taken from the interview, while the questionnaire and observation used as supporter or secondary data. The reseacher used wants analysis to find the students? need. The questions of the interview and questionnaire were designed and developed according to the evaluation domains. As the findings showed that the textbooks that are used in several senior high school in Parepare can be considered acceptable.